The Influence of Digital Literacy by Utilizing YouTube toward Students’ Speaking Ability - Khasanah, Makrifatul; Lestiyanawati, Rochyani (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2024)
Speaking is a complex skill in language learning, influenced by various internal and external factors. Learners often encounter challenges related to motivation, confidence, interest, environment, mother tongue use, and teaching methods. This research investigates the impact of using YouTube as a learning medium to enhance speaking skills in grade XI students at SMAN 1 Kaliwiro. Specifically, the study aims to (1) analyze the influence of digital literacy, facilitated by YouTube, on the speaking abilities of grade XI students and (2) compare the speaking abilities of students taught using YouTube to those taught using traditional methods. A quantitative experimental design was employed, involving 66 students (33 in class XI Science 2 and 33 in class XI Science 3). The school-based oral assessment (SBOA) form measured pre-test and post-test speaking performance. An independent sample t-test analysis was conducted using SPSS to compare the results. The findings reveal that students taught using YouTube demonstrated a moderately effective improvement in speaking skills, as indicated by a Normalized Gain Test score of 64.13 (64%). These results suggest that YouTube can be an effective tool for enhancing speaking abilities in language learners.